CT study of the performance of reciprocating and oscillatory motions in flattened root canal areas - Moura-Netto, Cacio; Palo, Renato Miotto [UNESP]; Pinto, Larissa Fernanda; Mello-Moura, Anna Carolina Volpi; Daltoé, Gisele; Wilhelmsen, Niels Salles Willo (Sociedade Brasileira de Pesquisa Odontológica - SBPqO, 2015)
Root canal preparation is an important step in endodontic treatment. The anatomical complexity of the middle third of the root compromises the effective cleaning of this area. Thus, advances have been made in instrumentation techniques and instruments for this purpose. The aim of this study was to evaluate the effects of three different instrumentation systems on the enlargement of the middle thirds of root canals in mandibular incisors. The preparation methods used were the reciprocating systems Reciproc (Group I) and WaveOne (Group II) and the oscillatory system Tilos (Group III). Comparisons were made by three-dimensional image reconstruction with cone-beam computed tomography before and after instrumentation. Changes in area, perimeter, centering ability, and pattern of preparation were analyzed. The results were subjected to ANOVA complemented by the Tukey’s test. Changes in area, perimeter, and tendency of transportation showed similar results among groups. The transportation index of the Tilos system was significantly lower than that of the other groups. Qualitative analysis of the preparation pattern showed that the Tilos system had a more uniform preparation, although Reciproc and WaveOne preparations appeared more rounded, incompatible with the original canal anatomy. There was similarity in the systems’ performance on flattened areas, although the Tilos system presented a better pattern of root canal preparation and a lower index of transportation.
Keywords: Root Canal Preparation; Dental Instruments; Endodontics